Marketing Strategies in Increasing Buying Interest and Customer Satisfaction in The Era of Digital Marketing Trends on Company Srawung Konveksi Malang City - Paskalia Anita Langgur; Gunawan, Cakti Indra; Setyaningrum, Fitria (International Journal of Management and Business, 2025)
The objective of this study is to analyze the marketing strategy of the Srawung Convection company in Malang City using the marketing mix approach. This research employs a qualitative descriptive method, with data collection techniques including observation, interviews, documentation, and triangulation. The informants in this study consist of one key informant and five supporting informants. The findings indicate that the marketing mix is an effective strategy in adapting to digital marketing trends. The role of the product in increasing consumer interest and satisfaction at Srawung Convection lies in maintaining product quality, including high-quality fabrics, attractive designs, and neat stitching that meets consumer expectations. The pricing strategy focuses on setting competitive prices in the market while ensuring alignment with product quality. The role of place in enhancing consumer interest and satisfaction at Srawung Convection is reflected in its strategic location in the city center, which facilitates production activities and consumer interactions. Promotion plays a crucial role in boosting consumer interest and satisfaction through both offline methods, such as word-of-mouth marketing, and online strategies using social media platforms like Instagram and Facebook. Therefore, the four key components of the marketing mix Product, Price, Place, and Promotion effectively contribute to increasing consumer interest and satisfaction, aligning with digital marketing trends at Srawung Convection in Malang.